(untitled) (Asian Journal of Pharmaceutics (AJP), 2025)
Regulatory science is essential for translating biomedical innovations into clinical applications. As translational medicine advances, regulatory frameworks must adapt to support emerging technologies and evolving healthcare models. Key challenges include integrating real-world evidence, regulating personalized therapies, managing digital health data, and harmonizing global standards for multinational trials. The rise of complex medical products demands agile regulatory approaches, such as adaptive trial designs, decentralized studies, and novel endpoints. Strengthening cross-disciplinary expertise and stakeholder engagement, including with patients and industry, is also crucial. Future directions emphasize risk-based, patient-centered strategies, global harmonization, and leveraging artificial intelligence in regulatory evaluation. By evolving with scientific progress, regulatory science can accelerate the safe and effective delivery of next-generation therapies to patients worldwide.